Taxonomic changes and an updated catalogue for the Palaearctic Sericini (Coleoptera: Scarabaeidae: Melolonthinae) - Ahrens, Dirk (Zootaxa, 2007)
This paper presents some results of the ongoing taxonomic investigations of the Asian Sericini (Scarabaeidae: Melolonthinae) beetle fauna with an updated catalogue to the Palaearctic members of this tribe. The following new synonymies and combinations are introduced: Archeohomaloplia Nikolajev, 1982 (= Melanomaladera Miyake & Yamaya, 2001, new synonymy); Trioserica Moser, 1922 (= Sinoserica Miyake & Yamaya, 2001, new synonymy); Nipponoserica koltzei (Reitter, 1897) (= Nipponoserica opacicarina Kim & Kim, 2003, new synonymy); Maladera lignicolor (Fairmaire, 1887) (= Autoserica laboriosa Brenske, 1897, Aserica fusiana Murayama, 1934, and Serica tenebrosa Frey, 1972, new synonymy); Neosericania nitida (Kobayashi, 1985) new combination; Eumaladera subrugata (Moser, 1926) new combination; Eumaladera opaciventris (Moser, 1915) new combination (= Maladera coreana Kim & Kim, 2003, new synonymy); Maladera verticalis (Fairmaire, 1888) (= Maladera castanea koreana Kim & Kim, 2003, new synonymy); Archeohomaloplia abbreviata (Fairmaire, 1897) new combination (= Areohomaloplia potanini Nikoleav, 1982, new synonymy); Archeohomaloplia yunnana (Miyake & Yamaya, 2001) new combination; Trioserica maculipennis (Miyake & Yamaya) new combination; Serica (Taiwanoserica) anmashana (Kobayashi, 1993) new combination; S. (T.) bihluhensis (Kobayashi & Yu, 2000) new combination; S. (T.) chunlinlii (Ahrens, 2002) new combination; S. (T.) elongata (Nomura, 1974) new combination; S. (T.) gracilipes (Nomura, 1974) new combination; S. (T.) kubotai (Kobayashi, 1983) new